Acoustic time-of-flight imaging of polymer electrolyte membrane water electrolysers to probe internal structure and flow characteristics. (23rd March 2021) - Maier, M.; Owen, R.E.; Pham, M.T.M.; Dodwell, J.; Majasan, J.; Robinson, J.B.; Hinds, G.; Shearing, P.R.; Brett, D.J.L.
Abstract: Acoustic time-of-flight (AToF) imaging has been demonstrated as a low-cost, rapid, non-destructive, operando tool to characterize processes in the flow channels and liquid-gas diffusion layer (LGDL) of polymer electrolyte membrane water electrolysers (PEMWEs). An array of 64 piezoelectric sensors was used, with all sensors emitting input pulses and detecting the acoustic wave reflected by the sample (pulse-echo mode). The shape and intensity of this reflected waveform depends on the ratio of reflection and transmission at phase interfaces and is strongly affected by resonant scattering of acoustic waves by gas bubbles. This AToF imaging technique was deployed to produce reflection intensity maps of the anode flow-field and LGDL; by measuring the AToF response for current densities ranging from 0.00 A cm −2 to 2.00 A cm −2, a close correlation was found between the acoustic attenuation in the flow-field and the production and removal of oxygen gas through the flow channels. Furthermore, a close link between the AToF response and water thickness in the LGDL was demonstrated, as supported by literature data. The application of the AToF technique has been established as a novel way of investigating PEMWE operation and as an alternative to more complex imaging techniques such as neutron imaging. Highlights: Operando acoustic time-of-flight imaging of a PEM water electrolyser. Novel diagnostic tool to investigate structural properties and mass transport. Acoustic reflection intensity decreases with increasing amounts of gas production. Link between neutron imaging studies and acoustic reflection intensity from LGDL.